PENGELOLAAN SUMUR GARAM DITINJAU DARI SEGI HUKUM ADAT DI DUSUN SUAK KECAMATAN SEPAUK KABUPATEN SINTANG - Genopepa Sedia (Universitas Kapuas Sintang, 2019)
Abstract Sintang Regency, West Kalimantan Province has an area of 21,635 Km2, the third largest in West Kalimantan Province after the Districts of Ketapang and Kapuas Hulu. One of the Sintang districts is intended to preserve local wisdom, the customs of the Dayak community for natural wealth, one of which is the existence of the Salt Well in the vicinity of Suak Hamlet, Manis Raya Village, Sepauk District. The purpose of this study is to identify and identify internal and external factors that influence the process of developing the well of the Salt Well tourism object and to overcome all the factors that become obstacles. Customary Institution is an Institution that has a Strategic to maintain Norms, customs that apply in indigenous peoples who become flesh and blood in the life of the Dayak tribe in general, one of which is applied at certain moments with a reception device and other rituals, one of them welcoming guests organized by the Dayak Indigenous Council at the sub-district level in Sintang District. Dayak “village” people must maintain the culture they have that comes from their ancestors even though they have embraced religion that is recognized by the government, but customs are born before religion exists so that it is worth guarding and preserved by indigenous people in general on the island of Kalimantan. Employees who are celebrations, for example, are disputed, bejereh, traditional mourning, tooth grinding, hair clippers and planting flowers and gadgets which are a means of resolving cases in the community which are commonly known in the community as the closing ceremony of the year or after the harvest season. Settlement of land boundaries dispute of Dayak indigenous people and customs rules in the village of Manis Raya in terms of maintaining and preserving the attractions of the Salt Well which is quite an indication of its existence. Keywords: Management, Salt Well, Customary Law.